PENGARUH MODEL PEMBELAJARAN BATU LONCATAN TERHADAP HASIL BELAJAR PKn SISWA KELAS VII SMPN 38 PEKANBARU - Sri Wahyuni; Sri Erlinda; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is conducted by low learning result of students of class VII SMPN 38 Pekanbaru. The formulation of the problem in this research is "Whether the learning model of stepping stone can affect the learning outcomes of Civics students of class VII SMPN 38 Pekanbaru." This study aims to determine the existing learning model in Batu Loncatan to the results of learning PKN students class VII SMPN 38 Pekanbaru. The research was conducted in class VII SMPN 38 Pekanbaru in January 2018 until May 2018. This research is a quantitative descriptive research which become source in this research that is student / student of class VII SMPN 38 Pekanbaru. The sample in this study was given 'Random Sampling' technique. Where the class is sampled is the students of class VII.2 (experimental class) which is given learning model of stepping stone, and class VII.3 (control class) are students using conventional method. Then data analysis by using homogeneity test and test "t". Based on the result of research indicate that there are student learning result using learning model of stepping stone and conventional method at SMPN 38 Pekanbaru, t_ (count)> t_ (table) (7,38> 2,00). Where there is average knowledge Learning outcomes of Cn class of experiment from 64 to 80,33 and average of result of learning of Cn class of control from 39,83 to 54,16. Thus the hypothesis which reads the limitations of the learning model of stepping stone to the students' learning outcomes at SMPN 38 Pekanbaru, is acceptable.Keywords: Stepping Stone, Results